VARIATION OVER TIME OF BIOINSECTICIDES EFFECT ON Spodoptera frugiperda INCIDENCE IN CORN (Zea mays) IN DRY SEASON IN MOCACHE, LOS RÍOS, ECUADOR - Ramiro Gaibor Fernández; Sergio Rodríguez Rodríguez; Juan José Reyes- Pérez; César Miguel Guevara Avilés; Paula Plaza Zambrano (Tropical and Subtropical Agroecosystems, 2023)
Background. Corn cultivation – one of the main crops in the world – is important in Ecuador for human and animal nutrition, but one of the main limitations in production is the damage caused by the insect pest Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae). Objective. Therefore, the objective of this research is to evaluate the effectiveness over time of three bio-insecticides on pest incidence in maize hybrid INIAP H601 in Mocache, Los Ríos, Ecuador in the dry season. Methodology. A completely randomized design was used with five treatments and four replicates: (1) Natural neem (Azadirachta indica) leaf extract in doses of 1.88 L; (2) Bassigeos (Beauveria bassiana) in doses of 5 L; (3) Neem + B. bassiana mix in doses of 7 L; (4) Chemical bait in doses of 80 kg.ha-1; and (5) Control group without application, processed by a linear model of repeated measures.  Results. A significant variation was observed in the treatments due to the influence of time. Implications. Corn agricultural production has a long tradition and importance in Ecuador, especially in the Province of Los Ríos where productions are affected by S. frugiperda whose major control is by using polluting chemical products.  Conclusions. Because the effect of the applied bio-insecticide treatments changes overtime, pest incidence is modified through a linear model of repeated measures. The lowest incidence percentages are achieved with the use of B. bassiana (Bb), A. indica (neem) and Bb + Neem mix after day 15, whereas the chemical control group achieves it throughout the evaluated time interval.